I understand : we move the first "2" left of Sigma, we replace "(h - i)" by "j" and "i" by "h - j"
Lower limit of i: i = 0 leads to j = h - 0 = h
Upper limit of i: i = h - 1 leads to j = h - (h - 1) = 1
Now, some of my own confusion. We currently have
The problem is that the original summation has that h is 1 or greater. The second summation has that h is 1 or less. I cannot make any headway for this part.
Notice that we no longer have that pesky problem with the earlier summation limits. I can't explain that one either.